Influence of copper-zinc mixture in different rates on pH and electrical conductivity as a potential for foliar spray fertilization (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
Electrical conductivity (EC) and pH of a nutrient solution influences the availability of nutrients, so it should be maintained in the optimum range. Nutrient solutions available to plants at low pH (between 5.0 and 6.0) and EC (between 1.6 and 2.4). Pineapple plants require copper and zinc micronutrients to produce high quality fruits. By applying different rates of copper-zinc chelated fertilizer with NPK fertilizer, it will help to increase the plant growth and nutrient uptake. 0.1,0.2,0.3,0.4,0.5 and 0.6 g of copper EDTA and zinc EDTA were added with 8.89 g nitrogen, 3.86 g phosphorus, and 2.18 g potassium. All the mixtures were diluted with 250 ml water. Electrical conductivity (EC) analysis was measured using the EC meter with calibrated conductivity meter while pH solution was measured using pH meter. Results from this study can be concluded that there was a significant difference between pH and EC reading. The optimum solution at 0.6 g rate of copper EDTA and zinc EDTA showed pH 5.74 and EC reading at 1.156 ms/m. The findings of this study showed that copper-zinc chelated fertilizer mixtures at different rates can affect the reading of pH and EC.
Keywords: electrical conductivity; chelated fertilizer